Placental and Maternal Serum Expression of sFlt-1 e15a and PlGF Reveal Distinct Angiogenic Patterns in Early-Onset Preeclampsia - Gustuti, Rina; Yusrawati; Azwan, Reyhan Julio; Uzlifah, Sara (International Journal of Statistics in Medical Research, 2026)
Background: Early-onset preeclampsia (EOPE) represents a severe pregnancy disorder occurring before 34 weeks of gestation and is strongly associated with impaired placental angiogenesis. This condition is characterized by an imbalance between antiangiogenic and proangiogenic factors, particularly soluble fms-like tyrosine kinase-1 (sFlt-1) e15a and placental growth factor (PlGF). Despite their recognized roles, data regarding the concurrent expression of these biomarkers in maternal serum and placental tissue remain limited. Methods: This analytical observational study used a comparative cross-sectional design involving 91 pregnant women with preeclampsia, categorized into EOPE (n=45) and late-onset preeclampsia (LOPE; n=46). Maternal serum and placental levels of sFlt-1 e15a and PlGF were measured using enzyme-linked immunosorbent assay (ELISA). Statistical analyses were performed using independent t-tests or Mann–Whitney tests depending on the data distribution. Receiver operating characteristic (ROC) analysis and Spearman correlation were conducted to evaluate diagnostic performance and biomarker relationships. Results: Serum sFlt-1 e15a levels were higher in EOPE than LOPE, although not statistically significant (p=0.082), while serum PlGF levels were significantly lower (p<0.001). Consequently, the serum sFlt-1/PlGF ratio was significantly elevated in EOPE (p<0.001). In placental tissue, sFlt-1 e15a levels were significantly lower, whereas PlGF levels were markedly reduced in EOPE compared to LOPE (both p<0.001), resulting in a higher placental sFlt-1/PlGF ratio (p<0.001). ROC analysis demonstrated good discriminative performance for both serum (AUC=0.772) and placental ratios (AUC=0.782). Significant correlations were observed between serum and placental biomarkers, particularly for the sFlt-1/PlGF ratio (ρ=0.859, p<0.001). Conclusion: EOPE is characterized by a pronounced angiogenic imbalance in both maternal serum and placental tissue. The sFlt-1/PlGF ratio demonstrates strong diagnostic potential and may serve as a reliable biomarker for early identification and risk stratification of EOPE.